V‐band injection‐locked oscillator with 9 GHz locking range. Issue 8 (1st April 2013) - Feng, C.; Yu, X.P.; Lu, Z.H.; Lim, W.M.; Sui, W.Q.
Abstract : An injection‐locked oscillator (ILO) with a self‐biased injection circuit is proposed. By using the series‐inductive peaking technique, the efficiency of the signal injection is considerably improved. Implemented in Global Foundries 65 nm bulk CMOS process, the proposed ILO demonstrated a 9 GHz locking range and can operate in 52–71 GHz with the tuning mechanism. Occupying a silicon area of 0.3 mm 2, the circuit draws 13 mA from a 1.2 V supply including the output buffers.